Identification of Salmonella isolated from freshwater mussels (Unio elongatulus eucirrus Bourguignat, 1860) by polymerase chain reaction - Seker, E; Sarieyyüpoglu, M; Çetinkaya, B (Scientific Technical Research Council Turkey, 2003)
In this study, 627 live freshwater mussels collected from the Kockale and Pertek regions of Keban Dam Lake were examined for the presence of Salmonella spp. Homogenates prepared from the soft tissue of mussels, after pre-enrichment in Rappaport Vasilliadis, were inoculated onto Brilliant Green Phenol Red Lactose agar and Salmonella-Shigella selective media. Biochemical tests and DNA extraction were carried out on isolates suspected of containing Salmonella. From 19 (4.8%) out of 397 mussels collected in the Ko kale region, Salmonella spp. were isolated and identified, but the agent could not be detected in mussels obtained from the Pertek region. DNA extracted from these isolates was amplified by polymerase chain reaction (PCR) using a pair of genus-specific primers derived from the 16S rRNA gene of Salmonella. Analysis of PCR products on agarose gel electrophoresis showed that the Salmonella specific gene was present in all 19 isolates. In conclusion, it was demonstrated that PCR, which has a very wide application field, could also be used in aquaculture for the identification of microbiological agents. Moreover, in the light of the data obtained in this study, the consumption of uncooked freshwater mussels living in the Kockale region of Keban Dam Lake may threaten public health.
Tatli su midyesinden (Unio elongatulus eucirrus Bourguignat, 1860) i?zole edilen Salmonella'larin Polimeraz Zincir Reaksiyonu (PZR) ile i?dentifikasyonu
Keywords: freshwater mussel; Salmonella; culture; polymerase chain reaction